The Four Postulates of Freudian Unconscious Neurocognitive Convergences - Arminjon, Mathieu (Frontiers in Psychology, 2011)
In the 80’s, the terms "cognitive unconscious" were invented to denominate a perspective on unconscious mental processes independent from the psychoanalytical views. For several reasons, the two approaches to unconscious are generally conceived as irreducible. Nowadays, we are witnessing a certain convergence between both fields. The aim of this paper consists in examining the four basic postulates of Freudian unconscious at the light of neurocognitive sciences. They posit: (1) the existence psychological processes unconsciously performed, (2) having their own cognitive style, (3) setting out their own intentions and (4) leading to a conflicting organization of psyche. We show that each of the postulates is the subject of empirical and theoretical works. If the two fields refer to more or less similar mechanisms, we propose that their opposition rests on an epistemological misunderstanding. As a conclusion, we promote a conservative reunification of the two perspectives.